PERSEPSI MASYARAKAT TERHADAP KEGIATAN KULIAH PENGABDIAN MASYARAKAT (KPM) - Andi Syahputra; Heri Rahmatsyah Putra (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2020)
Students as educated humans formed in tertiary education must certainly be tested for their maturity in meeting the tri dharma of tertiary institutions. One of them is by carrying out community service or community service lecture (CSL). But in its application, of course, the community has an assessment or perception of the presence of CSL students. Through this study, the writer tries to do a study on how the community's perception of the STAI Ar-Ridho student community service lecture activities in the Kepenghuluan Sungai Manasib. The formulation of the problem in this study is how people's perceptions of the fifth generation of STAI Ar-Ridho student service learning activities in Kepenghuluan Sungai Manasib, Bangko Pusako District. The purpose of this study was to determine public perceptions of the fifth generation of STAI Ar-Ridho student service learning activities in the Kepenghuluan Sungai Manasib Bangko Pusako District. Through descriptive qualitative research methods that describe in depth about what is obtained from informants. The author uses the subject and research informants are the apparatus of knowledge and community knowledge of the Manasib River. From the results of this research, it was found that the perception of the Manasib River pengululuan community towards CSL students was very good and supported all kinds of activities carried out during that time both for the development and development of the Sungai Manasib zoning area. Of course the mindset and public understanding of the things conveyed by students are not all understood, but the community still supports positive activities by STAI Ar-Ridho CSL students.